Methodology, selection, and integration of fracture healing assessments in mice. Issue 11 (10th September 2021) - Knox, Adam M.; McGuire, Anthony C.; Natoli, Roman M.; Kacena, Melissa A.; Collier, Christopher D.
Abstract: Long bone fractures are one of the most common and costly medical conditions encountered after trauma. Characterization of the biology of fracture healing and development of potential medical interventions generally involves animal models of fracture healing using varying genetic or treatment groups, then analyzing relative repair success via the synthesis of diverse assessment methodologies. Murine models are some of the most widely used given their low cost, wide variety of genetic variants, and rapid breeding and maturation. This review addresses key concerns regarding fracture repair investigations in mice and may serve as a guide in conducting and interpreting such studies. Specifically, this review details the procedures, highlights relevant parameters, and discusses special considerations for the selection and integration of the major modalities used for quantifying fracture repair in such studies, including X‐ray, microcomputed tomography, histomorphometric, biomechanical, gene expression and biomarker analyses.